Clinical benefits and complication profile of IL-23 inhibitors in patients with psoriatic arthritis: a systematic review and meta-analysis - Zeng, Jingxin; Lin, Ling; Li, Wei; Gao, Xinjing; Li, Qian; Zhou, Xin; Liu, Weiyu; Zhong, Xuelian; Yang, Yunqing; Zhang, Xibao; Luo, Quan (Frontiers in Pharmacology, 2025)
BackgroundPsoriatic arthritis (PsA) is a chronic inflammatory disease with heterogeneous manifestations affecting both joints and skin. Interleukin-23 (IL-23) plays a central role in the Th17-mediated inflammatory pathway implicated in PsA pathogenesis. This meta-analysis aimed to evaluate the clinical efficacy and safety profile of IL-23 inhibitors in the treatment of PsA.MethodsA systematic literature search was conducted across PubMed, Embase, Web of Science, and Cochrane Library up to June 30, 2025, adhering to PRISMA guidelines. Randomized controlled trials (RCTs) involving adult Psoriatic Arthritis (PsA) patients treated with IL-23 inhibitors versus placebo were included. Key outcomes analyzed included American College of Rheumatology (ACR) 20, 50, and 70 responses, Psoriasis Area and Severity Index (PASI) 90, minimal disease activity (MDA), and enthesitis and dactylitis resolution.ResultsSix RCTs involving IL-23 inhibitors were included. IL-23 inhibitors significantly improved ACR20 (RR = 1.86; 95% CI: 1.69–2.05), ACR50 (RR = 2.75; 95% CI: 2.31–3.29), and ACR70 (RR = 3.06; 95% CI: 2.29–4.10) responses. Skin clearance (PASI90) was markedly higher (RR = 5.98; 95% CI: 4.68–7.64). IL-23 inhibition also resulted in superior MDA (RR = 2.85; 95% CI: 2.30–3.54), and better resolution of enthesitis (RR = 1.46; 95% CI: 1.29–1.64) and dactylitis (RR = 1.39; 95% CI: 1.20–1.61). Publication bias was not detected.ConclusionIL-23 inhibitors are effective in improving musculoskeletal and dermatologic outcomes in PsA, supporting their role in comprehensive treatment strategies. Further long-term comparative studies are needed.Systematic Review Registrationclinicaltrials.gov, identifier CRD420251169783.